Quantifying the extent of morphological homoplasy: A phylogenetic analysis of 490 characters in Drosophila. Issue 3 (22nd April 2019) - Al Sayad, Sinan; Yassin, Amir
Abstract: Homoplasy is a fundamental phenomenon in evolutionary biology but an appraisal of its extent at the morphological level is still lacking. Here, we analyzed the evolution of 490 morphological characters conceptualized among 56 drosophilid species. We found that two thirds of morphological changes were homoplastic and that the level of homoplasy depended on the stage of development and the type of the organ, with the adult terminalia being the least homoplastic. In spite of its predominance at the character change level, homoplasy accounts for only ∼13% of between species similarities in pairwise comparisons. These results provide empirical insights on the limits of morphological changes and the frequency of recurrent evolution.